The Effect of Firm Size and Institutional Ownership on Tax Avoidance: Case Studies of Manufacturing Companies in the Consumer Goods Sector Listed on the Indonesia Stock Exchange for the 2017-2021 period - Bani Binekas; Ajeng Ayuning Tyas (Profesional Muda Cendekia Publishing, 2023)
This study aims to determine the effect of firm size and institutional ownership on tax avoidance. This research method in this study uses a quantitative approach with SPSS analysis tools. The population in this study are consumption goods sector listed in Indonesia Stock Exchange (IDX) with secondary data in the form of Annual Report of consumption goods sector manufacturing companies in 2017-2021. The sampling method used is purposive sampling method with a sample of 32 manufacturing companies consisting of 4 sub-sectors of the company that were sampled in this study. The analysis method of this study uses multiple linear regression. The result of this study indicate that firm size has effect on tax avoidance. Therefore, institutional ownership has no effect on tax avoidance.